Vaccines the History and Future - Kumar, Vijay (IntechOpen, 2019)
Vaccines is a well-written book on the subject of providing crucial information to students and researchers in the field of vaccinology. The introductory chapter, contributed by the editor (Dr. Vijay Kumar) of the book, provides the brief introduction to the history of the development of current forms of vaccine, which is difficult to find easily in one place. In addition, other chapters of the book are written by experts in the field. For example, the second chapter looks at the emerging role of developing countries in the innovation and production of vaccines. Other chapters provide information regarding different types of vaccines, development of vaccines for zoonotic viral infections, and regulatory affairs for genetically modified organism vaccines.